Risk relevance of psychometric assessment and evaluator ratings of dynamic risk factors in high-risk violent offenders - Higgs, Tamsin (Legal and criminological psychology, 2020)
PURPOSE-Relatively little research has been conducted with high-risk violent (non-sexual) offenders to establish whether measures administered to evaluate change during offending behaviour programmes contain risk relevant information. The present study aims to contribute to the evidence base relevant to decisions concerning whether or not psychometric assessments indicate how the violence risk presented by an individual may be understood differently pre- to post-treatment.METHODS-Two hundred and twenty-seven persistently violent offenders participating in Correctional Service of Canada’s Violence Prevention Program were assessed on measures of anger, impulsivity, and dynamic items of the Violence Risk Scale (VRS; Wong & Gordon, 1999–2003; Violence Risk Scale, University of Saskatchewan, Saskatchewan, CA) prior to and after programme completion and subsequently followed up in the community for an average of 3 years. Data were examined using receiver operating characteristic and logistic regression analyses employing fixed follow-ups.RESULTS-With pre-treatment status controlled, change on few of the measures convincingly predicted violent or general recidivism. An exception was that changes in VRS dynamic score were associated with decreased general (but not violent) recidivism, controlling for baseline pre-treatment risk.CONCLUSIONS-The measures tested are widely used to evaluate progress in violence interventions yet the implicit assumption that they contain risk relevant information has not been empirically validated. Since reduction in dynamic risk factors translates into reduced likelihood of reoffending, but psychometric measures provide little indication of change in recidivism risk, treatment providers are advised to carefully contextualize pre- to post-treatment change within a comprehensive evaluation of static and dynamic risk using a measure such as the VRS. Present results are discussed further in terms of implications for policy and clinical practice, as well as future research directions.